Bilayered extracellular matrix derived scaffolds with anisotropic pore architecture guide tissue organization during osteochondral defect repair - Buckley, Conor; Kelly, Daniel (My University, 2022)
While some clinical advances in cartilage repair have occurred, osteochondral (OC) defect repair remains a significant challenge, with current scaffold-based approaches failing to recapitulate the complex, hierarchical structure of native articular cartilage (AC). To address this need, we fabricated bilayered extracellular matrix (ECM)-derived scaffolds with aligned pore architectures. By modifying the freeze-drying kinetics and controlling the direction of heat transfer during freezing, it was possible to produce anisotropic scaffolds with larger pores which supported homogenous cellular infiltration and improved sulfated glycosaminoglycan deposition. Neo-tissue organization in vitro could also be controlled by altering scaffold pore architecture, with collagen fibres aligning parallel to the long-axis of the pores within scaffolds containing aligned pore networks. Furthermore, we used in vitro and in vivo assays to demonstrate that AC and bone ECM derived scaffolds could preferentially direct the differentiation of mesenchymal stromal cells (MSCs) towards either a chondrogenic or osteogenic lineage respectively, enabling the development of bilayered ECM scaffolds capable of spatially supporting unique tissue phenotypes. Finally, we implanted these scaffolds into a large animal model of OC defect repair. After 6 months in vivo, scaffold implantation was found to improve cartilage matrix deposition, with collagen fibres preferentially aligning parallel to the long axis of the scaffold pores, resulting in a repair tissue that structurally and compositionally was more hyaline-like in nature. These results demonstrate how scaffold architecture and composition can be spatially modulated to direct the regeneration of complex interfaces such as the osteochondral unit, enabling their use as cell-free, off-the-shelf implants for joint regeneration. Statement of significance The architecture of the extracellular matrix, while integral to tissue function, is often neglected in the design and evaluation of regenerative biomaterials. In this study we developed a bilayered scaffold for osteochondral defect repair consisting of tissue-specific extracellular matrix (ECM)-derived biomaterials to spatially direct stem/progenitor cell differentiation, with a tailored pore microarchitecture to promote the development of a repair tissue that recapitulates the hierarchical structure of native AC. The use of this bilayered scaffold resulted in improved tissue repair outcomes in a large animal model, specifically the ability to guide neo-tissue organization and therefore recapitulate key aspects of the zonal structure of native articular cartilage. These bilayer scaffolds have the potential to become a new therapeutic option for osteochondral defect repair.
Keywords: cartilage repair; osteochondral (OC) defect repair; bilayered extracellular matrix (ECM)-derived scaffolds; cartilage repair; osteochondral (OC) defect repair; bilayered extracellular matrix (ECM)-derived scaffolds